2022
DOI: 10.3389/fonc.2022.955830
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A Inhibits the Malignant Progression of Epithelial Ovarian Cancer by Affecting the MicroRNA-374b-5p/HMGB3/Wnt-β-Catenin Pathway Axis

Abstract: ObjectiveGlaucocalyxin A (GLA) is an ent-kaurene diterpenoid from Rabdosia japonica var possessing anti-tumor activity. This study aimed to investigate effects of GLA on epithelial ovarian cancer (EOC) and elucidate underlying mechanisms.MethodsThe expression of HMGB3 in EOC tissues was analyzed by GEPIA and immunohistochemistry. Cell proliferation was determined using CCK-8 and colony formation assays. Cell invasion, migration, and apoptosis were detected using Transwell, wound healing, and flow cytometry ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The results demonstrated that the OS of the high ITIH3 protein expression level group was significantly higher than the low ITIH3 protein expression group. Furthermore, in a preliminary study (5,23), the association between ITIH3 protein expression levels and key Bcl-2 signaling pathway proteins, as well as the OS of patients with high and low protein expression levels of Bcl-2 in OC were assessed using The Cancer Genome Atlas database (24). The results demonstrated that the protein expression levels of Bcl-2 were not significantly associated with to prognosis in OC tissues without chemotherapy (data not shown), therefore the Bcl-2 protein expression of TMAs was not assessed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the OS of the high ITIH3 protein expression level group was significantly higher than the low ITIH3 protein expression group. Furthermore, in a preliminary study (5,23), the association between ITIH3 protein expression levels and key Bcl-2 signaling pathway proteins, as well as the OS of patients with high and low protein expression levels of Bcl-2 in OC were assessed using The Cancer Genome Atlas database (24). The results demonstrated that the protein expression levels of Bcl-2 were not significantly associated with to prognosis in OC tissues without chemotherapy (data not shown), therefore the Bcl-2 protein expression of TMAs was not assessed in the present study.…”
Section: Discussionmentioning
confidence: 99%